Morfogênese do capim-marandu sob estratégias de rebaixamento para o diferimento - Oliveira, Davi Moraes de (2024)
The objective of the work was to verify how pasture lowering strategies before the differential stockpiling impact the morphogenesis of marandu grass throughout this period, as well as to determine the morphogenic, structural and productive differences between the basal and aerial tillers of marandu grass. The work was conducted from November 2021 to June 2022, at Capim Branco Experimental Farm, at Federal University of Uberlândia, in Uberlândia, MG. The treatments were applied according to a particularly randomized design, with three replications, and consisted of three pasture conditions for five months before the difference period: LC-15: continuous stocking with 15 cm average height; LC-35/15: continuous capacity with an average height of 35 cm in November 2022, with gradual lowering to 15 cm until the differential start date; LI-25/15: intermittent stocking 25 cm high pre-grazing and 15 cm high post-grazing. The stockpiling period began on 03/15/2022, which ended on 06/14/2022 (90 days). The lowering strategies for stockpiling did not modify the morphogenesis of stockpiled marandu grass. Maturity, elongation and leaf sensitivity rates, as well as all canopy development characteristics, decreased from the beginning to the end of the deferral period. The life span of the leaf, the length of the leaf and the length of the stem met the opposite response pattern. All morphogenic, structural and canopy development characteristics were superior in the basal tiller, compared to the aerial tiller. Marandu grass morphogenesis and canopy growth decrease throughout the period of stockpiling. Unlike the basal tiller, the aerial tiller has less development, occurs in fewer numbers, is less robust and has a low contribution to the growth of the deferred Marandu grass canopy.